Tindak Tutur Masyarakat di Pasar Raya MMTC, Medan - Cicilia Gultom; Enjelita Hutagalung; Hasea Simanjuntak; Lentiar Gultom; Mayesa Purba; Nazwa Pasaribu; Sarah Siregar (Universitas Serambi Mekkah, 2025)
This study aims to analyze the use of speech acts in buying and selling interactions at Pasar Raya MMTC Medan. This market was chosen as the research location because it is often visited by local people and people from outside the area, and the majority of interactions in the market use Indonesian, which makes it easier for researchers to understand the speech acts that occur. This study uses a qualitative method with observation, recording, and note-taking techniques to collect data. The main focus of the study is on the analysis of the types of speech acts used by traders and buyers in their daily interactions. The results of the study show that the speech acts used in this market tend to be polite, friendly, and full of joy, reflecting the values of local culture that are maintained. In addition, traders also use regional languages and Indonesian alternately to create social closeness with buyers. The principles of cooperation and the principles of politeness are seen in the interactions that occur, which make communication run smoothly and effectively. This study also reveals that politeness in language plays an important role in creating harmonious social relationships in traditional markets, where language is an important tool in bringing sellers and buyers closer together